Public knowledge and attitudes towards Human Papilloma Virus (HPV) vaccination - Powell Judy E; Sharma Amit; Shah Meeraj; Gera Aradhana; Walsh Charlotte; Wilson Sue (BMC, 2008)
Abstract Background Human Papilloma Virus (HPV) vaccine has undergone successful trials and has recently been approved for use for the primary prevention of cervical cancer. The aim of this study was to determine knowledge and attitudes towards HPV vaccination. Methods Semi-structured interview and questionnaire delivered in a street survey. Standardised HPV-related statements used to measure HPV knowledge and attitudes to vaccination. The setting was three different areas of Birmingham, to target a mix of social class and ethnicity. The sample population was composed of 16-54 year olds. Results A total of 420 participants were recruited. Poor knowledge of HPV and its links with cervical cancer were observed. 81% had a knowledge score of zero. Knowledge about HPV was associated with different ethnic group and socio-economic group. The majority (88%) of participants were in favour of vaccination, with 83.6% indicating that they would allow a child under their care to be vaccinated. Conclusion Initial responses to the proposed HPV vaccination within the UK public are favourable. However, knowledge levels are poor and media and health professional promotion are required to raise awareness.